Valorization of Betalain Pigments Extracted from Phytolacca americana L. Berries as Natural Colorant in Cheese Formulation - Ionuț Dumitru Veleșcu; Ioana Cristina Crivei; Andreea Bianca Balint; Vlad Nicolae Arsenoaia; Alexandru Dragoș Robu; Florina Stoica; Roxana Nicoleta Rațu (Agriculture)
In response to consumer demand for more sustainable and health-conscious products, the food sector is increasingly shifting towards the use of natural additives. Pokeweed (Phytolacca americana L.) is a medicinal plant that contains valuable biologically active compounds, including betacyanins, which serve as its red pigments, along with phenolic acids, flavonoids, polyphenolic compounds, and others. Phytolacca americana (P. americana) is a plant renowned for its bioactive compounds, which exhibit anti-inflammatory, anti-mutagenic, antioxidant, anticancer, and antibacterial properties. This study investigates the potential of betalain pigments extracted from the berries of P. americana as a natural colorant for cheese formulation. The impact of these pigments on the color attributes, sensory qualities, and physicochemical and phytochemical composition of the cheeses was systematically evaluated. The Phytolacca americana (PA) powder demonstrated significant levels of total polyphenols (111.95 ± 1.60 mg GAE/g dw) and antioxidant activity (21.67 ± 0.19 µmol TE/g dw). The incorporation of PA powder increased the physicochemical and phytochemical contents and antioxidant activity in the final product (4.40 ± 0.22 µmol TE/g dw for CPAP1 and 6.11 ± 0.22 µmol TE/g dw for CPAP2). The sensory study revealed that the PA-supplemented cheeses were acceptable. The enhanced cheeses present a distinctive color profile, attracting health-conscious consumers looking for innovative dairy products. The study concludes that PA powder can effectively enhance cheese, producing a phytochemical-enriched product that appeals to health-conscious consumers.